Effects of ultrasound-assisted sulfuric acid treatment on the decontamination of Co nuclides in cement paste simulating radioactive concrete waste from dismantled nuclear power plants. (10th April 2023) - Cho, Seongmin; Park, Jaeyeon; Suh, Heongwon; Kim, Gyeongryul; Lim, Jun; Seok, Seungwook; Bae, Sungchul
Graphical abstract: Highlights: Studied efficiency of cement paste decontamination using H2 SO4 and ultrasonication. Identified morphological and chemical characteristics of Co nuclides in cement paste. Decontamination efficiency was enhanced by applying ultrasonication. Clarified reaction mechanisms of decontamination using acid and ultrasonication. Abstract: This study proposes an ultrasonic treatment method for enhancing the decontamination efficiency of cement waste under the lower acid concentration. The phase transitions and decontamination efficiency of the hydrates and Co nuclides in the cement paste were respectively studied using various concentrations of sulfuric acid. The effect of pre-heating the acid-treated cement paste at 500 ℃ on its phase transition and decontamination efficiency were also studied. The underlying mechanism of the enhanced decontamination efficiency was elucidated by inductively coupled plasma spectrometry, powder X-ray diffraction, thermogravimetry, laser diffractometry, and X-ray absorption spectroscopy. Ultrasound-assisted decontamination by 1.0 M H2 SO4 was 1.5 times more efficient than non-sonication-assisted decontamination with double the acid concentration (2.0 M H2 SO4 ), owing to the detachment of the outer-layer phases of CaSO4 that obstructed the contact between the acid and the nuclides. The thermally-treated samples showed similar decontamination efficiencies under treatment with high acid concentrations and ultrasonication, due to the vigorous acid reaction kinetics regardless of the thermal decomposition of the hydrates.